Analisis Perbandingan Pendapatan Usaha Penggilingan Padi Menetap dan Keliling di Desa Pematang Johar. Kecamatan Labuhan Deli - Adelina Purba; Gustami Harahap; Khairul Saleh (Jurnal Ilmiah Pertanian ( JIPERTA), 2021)
This study aims to determine: analyze business income settled rice mill and roving rice mill, analyze business income comparison settled rice mill and roving rice mill. Sampling method for rice milling business census method. Based on this study set as many 13 rice milling business is the respondent. Data analysis method used is Uji Mann-Whitney with software tools SPSS 21. The results of the study showed the average income rice milling business settled for Rp 5.649.821 per 26 day as for the average income roving rice mill Rp 6.355.760 per 26 day, and for income differences uji Mann-Whitney U is 0,398. Where with results uji Mann-Whitney 0,398 there is no difference in income in permanent rice milling business and roving rice milling.